2011
DOI: 10.1007/s11458-011-0253-6
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of silica-polymer hybrids via simultaneous RAFT process and hydroxyl-alkoxysilane coupling reaction

Abstract: This study aimed at the synthesis of silica particles grafted with better-defined homopolymers and block copolymers by tandem approach. Z-functionalized Sbenzyl S'-(3-trimethoxysilyl)propyltrithiocarbonate (BTPT) was used as a couplable RAFT agent to synthesize the target inorganic-organic hybrids. Simultaneous coupling reaction and RAFT process using silica particles and BTPT as raw materials efficiently afforded homopolymers grafted silica, and RAFTsynthesized macro chain transfer agents with ω-terminal trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The one-pot method comprising concurrent coupling reaction and controlled radical polymerization has been proven efficient to generate well-defined polymers grafted solid substrates such as silica particles and graphene oxide. 16,[30][31][32] Our previous studies revealed that the quaternization reaction and RAFT polymerization could be simultaneously conducted to construct complex macromolecular architectures such as miktoarm star and toothbrushlike copolymers. [72][73][74] Herein tandem quaternization and RAFT processes were used to generate toothbrushlike copolymer grafted silica, in which the side chains were formed during concurrent coupling and polymerization based on BBCP, and the handle comprising linear chains was generated by chain extension polymerization mediated by the terminal dithiobenzoate moieties of PDMA grafts.…”
Section: Synthesis Of Quaternized Toothbrushlike Copolymers Grafted S...mentioning
confidence: 99%
See 2 more Smart Citations
“…The one-pot method comprising concurrent coupling reaction and controlled radical polymerization has been proven efficient to generate well-defined polymers grafted solid substrates such as silica particles and graphene oxide. 16,[30][31][32] Our previous studies revealed that the quaternization reaction and RAFT polymerization could be simultaneously conducted to construct complex macromolecular architectures such as miktoarm star and toothbrushlike copolymers. [72][73][74] Herein tandem quaternization and RAFT processes were used to generate toothbrushlike copolymer grafted silica, in which the side chains were formed during concurrent coupling and polymerization based on BBCP, and the handle comprising linear chains was generated by chain extension polymerization mediated by the terminal dithiobenzoate moieties of PDMA grafts.…”
Section: Synthesis Of Quaternized Toothbrushlike Copolymers Grafted S...mentioning
confidence: 99%
“…Surface-initiated controlled radical polymerization techniques involving reversible addition-fragmentation chain transfer (SI-RAFT) polymerization have been efficiently used to prepare silica-polymer hybrid materials, in which the graft reaction can be conducted via either "grafting to" or "grafting from" approach. [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] The former affords a straightforward route to give the target hybrids with relatively low grafting density due to steric hindrance, whilst the latter allows the formation of silica-polymer hybrids with a higher grafting density although side reactions may lead to structural defects of grafted chains. SI-RAFT can be performed via either stepwise or tandem approach, however, the examples on tandem synthesis of polymer grafted solid substrates are very scarce thus far.…”
mentioning
confidence: 99%
See 1 more Smart Citation